2020
DOI: 10.1109/access.2020.3040418
|View full text |Cite
|
Sign up to set email alerts
|

Mowing Patterns Comparison: Analyzing the Mowing Behaviors of Elderly Adults on an Inclined Plane via a Motion Capture Device

Abstract: Due to the declining population and the aging of the farmer population in the hilly and mountainous areas of Japan, it is necessary for the elderly to carry out the mowing work on the ridges and slopes, which is traditionally regarded as heavy labor as part of paddy farming. One of the most important causes of these accidents is an incorrect mowing posture; therefore, it is important and necessary to identify effective and safe working patterns during inclined plane mowing. In this paper, we designed and imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The results showed that different postures were affected significantly (p < 0.05).The average UW speed was measured at 2.29 ± 0.53 m/s, the average SW travel speed was measured at 2.07 ± 0.62 m/s, and the average KHC travel speed was measured at 0.58 ± 0.20 m/s. The average bipedal walking velocity measured during this study was faster than the velocity of children measured in previous studies [12,21,22]. This study focused on individual behavior rather than group behavior, which would be less likely to collide.…”
Section: Discussion and Limitationmentioning
confidence: 63%
See 2 more Smart Citations
“…The results showed that different postures were affected significantly (p < 0.05).The average UW speed was measured at 2.29 ± 0.53 m/s, the average SW travel speed was measured at 2.07 ± 0.62 m/s, and the average KHC travel speed was measured at 0.58 ± 0.20 m/s. The average bipedal walking velocity measured during this study was faster than the velocity of children measured in previous studies [12,21,22]. This study focused on individual behavior rather than group behavior, which would be less likely to collide.…”
Section: Discussion and Limitationmentioning
confidence: 63%
“…Following the same calculation, other joints can be obtained. Excluding the angles for the chest and neck, the data for the other joints were collected in pairs (e.g., right and left ankle) 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the continuous development of sensors and Internet of Things (IoT) technologies, most human activities, including body movements [ 7 ], eye movements [ 8 ], and even activities on the Internet [ 9 ], can be dynamically acquired and analyzed. Among them, motion-capture devices, which can save a series of human movements as analyzable data through sensors, have been widely used in a variety of studies.…”
Section: Introductionmentioning
confidence: 99%
“…According to relevant studies [ 11 ] and related interviews with mowers in our previous works [ 7 , 12 ], personal factors such as age and physique may affect the stability of mowing behaviors, especially for physically demanding tasks like mowing on slopes. To ensure the safety of older workers, it is also necessary to study the effects of personal factors on older workers’ body movements while mowing on slopes.…”
Section: Introductionmentioning
confidence: 99%